Efforts to Improve Basic Motion Capabilities Non-Locomotor for Double Handicap Student Using Adaptive Game Application - Silmi Forestry (Indonesian Journal of Disability Studies, 2018)
The purpose of this study was to improve non-locomotor basic movement capability by applying adaptive games for multiple handicapped students of Class IV SLB A YKAB Surakarta in 2015.The method used in this study was experimental method using single subject research (SSR). Subject is multiple handicapped of blind and celebral palsy spectrum. This study employed A-B-A design involving three stages. The first was deciding baseline 1; the second was giving intervention; and the last was measuring the baseline 2. The data were colected through observations and analyzed using the analysis technique of descriptive qualitative data.The results of this study indicated that the scores got from observations were improved. The improvement was showed by the measurement of baseline 1 in which the average score was 57.8, then after the intervention of applying adaptive games, the average score was improved to 81.56. Moreover, the average score from baseline 2 which was not given any intervention was78.75. Based on the results of this study, the application of adaptive games can improve non-locomotor basic movement capability on multiple handicapped students of Class IV SLB A YKAB Surakarta in 2015.